Primary bronchial carcinoma associated with bone marrow metastasis and paraneoplastic monoclonal gammopathy in a cat. Issue 2 (September 2016) - Cervone, Mario; Beurlet, Stéphanie
Case summary: Herein we describe an unusual metastatic pattern and paraneoplastic manifestation of a bronchial carcinoma in a cat. An 8 year-old cat presented with a diminished appetite, dysphagia, weight loss, lethargy and coughing. Thoracic radiographs revealed a lung mass. Bronchial carcinoma was diagnosed on the basis of histology and was associated with a lymphoplasmocytic infiltration of the fibrovascular stroma. Biochemistry showed hyperproteinaemia. Serum protein electrophoresis showed a narrow spike in the gamma region. Bone marrow cytology revealed an infiltrate with numerous clustered epithelial cells. The cat was euthanased 2 months later because of anorexia and poor general condition. Relevance and novel information: To the best of our knowledge, this is the first clinical description of primary bronchial carcinoma associated with bone marrow metastases and paraneoplastic monoclonal gammopathy in a cat.